Carbon-coated nickel-based catalyst as well as rapid preparation method and application thereof

Through the rapid preparation method of carbon-coated nickel-based catalyst, the problems of complex preparation process and insufficient time-consuming, catalytic activity and selectivity in the prior art are solved, and efficient and low-cost catalyst preparation is achieved, which significantly improves the catalytic performance of pyrolysis of biomass hydrogen production.

CN119549152APending Publication Date: 2025-03-04XIAMEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411784169.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In actual application, the existing nickel-based catalysts and their diversified modification strategies have problems such as complex preparation process and long time-consuming, insufficient catalytic activity and selectivity, which is difficult to meet the efficient needs of biomass pyrolysis hydrogen production technology.

Method used

A rapid preparation method of carbon-coated nickel-based catalyst is used to prepare a catalyst with high activity and good selectivity through mixing, evaporation and drying, grinding and high-temperature heating. The method includes uniformly mixing the nickel precursor, other metal element precursors and catalyst support in a solvent, evaporate and heat treatment at high temperature to form carbon-coated nickel-based nanoparticles.

Benefits of technology

The catalyst is quickly, simple and large-scale preparation, with small particles and uniform size distribution, and appropriate carbon layer coating on the surface, which significantly improves catalytic activity and selectivity. It is suitable for the production of hydrogen by pyrolysis of biomass and demonstrates excellent catalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549152A_ABST
    Figure CN119549152A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts, in particular to a carbon-coated nickel-based catalyst and a rapid preparation method and application thereof. The preparation method comprises the following steps: adding a nickel precursor, other metal element precursors and a catalyst carrier into a solvent, and uniformly dispersing to form a mixture; heating and stirring the mixture at a certain temperature until the solvent is evaporated to dryness; grinding the evaporated product to obtain mixture powder; and carrying out rapid heating treatment on the mixture powder at a rapid heating rate, and cooling to obtain the product. According to the scheme, the high-performance nickel-based catalyst can be efficiently prepared in a large scale within a short time, the time consumed by single-time preparation is short, and the process is simple, convenient and rapid; the prepared catalyst is small in particle and relatively uniform in size distribution, meanwhile, a layer number controllable carbon coating is formed on the surface of the catalyst, and the catalyst has high activity and good selectivity, shows excellent catalytic performance in the application of biomass pyrolysis for hydrogen production, and thus has wide application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of catalyst technology, and in particular to a carbon-coated nickel-based catalyst and a rapid preparation method and application thereof. Background Art

[0002] As the global energy crisis and environmental problems become increasingly serious, the development and utilization of clean and renewable energy has become a global research focus. As one of the most abundant renewable resources on earth, biomass has attracted much attention in the field of hydrogen production due to its wide range of sources and carbon neutrality. Biomass pyrolysis is an effective hydrogen production technology that decomposes biomass raw materials into hydrogen-rich gas by heating them under oxygen-free or low-oxygen conditions. This process can not only effectively utilize biological resources such as agricultural waste, but also reduce dependence on fossil fuels, reduce greenhouse gas emissions, and promote carbon recycling.

[0003] Although traditional biomass pyrolysis technology can produce hydrogen, it still has great limitations in terms of efficiency and hydrogen yield. In particular, the gas produced by the conventional pyrolysis process contains a variety of impurities, and the hydrogen purity is low, requiring subsequent purification treatment. In addition, the yield of hydrogen is limited and it is difficult to meet the needs of large-scale applications. In order to increase the yield and purity of hydrogen, researchers have developed catalytic pyrolysis technology. By introducing catalysts, it can not only accelerate the pyrolysis reaction rate, but also significantly improve the output and quality of hydrogen. In this type of technology, nickel-based catalysts have become one of the research focuses due to their excellent catalytic performance and relatively low cost. Nickel-based catalysts can promote the breaking of carbon-hydrogen bonds in biomass, improve the efficiency of hydrogen generation, and reduce the generation of by-products.

[0004] Compared with single metal catalysts, multi-element nickel-based catalysts have better performance. By introducing other metal elements, such as copper, cobalt, molybdenum, etc., into nickel-based catalysts, the activity, stability and anti-carbon deposition ability of the catalyst can be further enhanced. The synergistic effect of these multi-element metals can not only improve the catalytic conversion efficiency of nickel-based catalysts for complex components in biomass, but also effectively inhibit the deactivation of catalysts in high-temperature pyrolysis environments. For example, the introduction of cobalt can improve the catalytic activity of nickel, while molybdenum can increase the sulfur resistance and oxidation resistance of the catalyst, thereby extending its service life. Multi-element nickel-based catalysts can therefore achieve higher hydrogen yields and better product selectivity during biomass pyrolysis.

[0005] However, existing nickel-based catalysts and their diversified modification strategies still face a series of problems in practical applications. Traditional catalyst preparation methods are usually complicated and time-consuming, making it difficult to achieve large-scale economic production. For example, existing preparation methods usually require several hours of high-temperature treatment steps. In addition, the activity and selectivity of the catalyst during the reaction process still need to be further improved to cope with the diversity and complexity of different types of biomass raw materials.

[0006] Therefore, developing an efficient and low-cost method for the rapid preparation of multi-element nickel-based catalysts, especially the preparation of catalysts with both high activity and good selectivity, is crucial to improving the efficiency and feasibility of biomass pyrolysis hydrogen production technology. This can not only promote the commercial application of biomass hydrogen production technology, but also provide a new technical path for the sustainable development of clean energy. Summary of the invention

[0007] In order to solve the problems of the prior art mentioned in the above background technology, the present application provides a method for rapidly preparing a carbon-coated nickel-based catalyst, and its technical solution is as follows: The rapid preparation method of the carbon-coated nickel-based catalyst provided in the present application comprises the following steps: Mixing: adding nickel precursor, other metal element precursors and catalyst carrier into the solvent and dispersing them evenly to form a mixture; Evaporation to dryness: placing the mixture under heating and stirring at a certain temperature until the solvent is evaporated to dryness; Grinding: Grind the evaporated product to obtain a mixture powder; High temperature heating: subjecting the mixture powder to high temperature heating treatment, and obtaining the carbon-coated nickel-based catalyst after cooling; The temperature rise curve of the high temperature heating treatment is: heating from room temperature to 700-1600°C at a heating rate of 25-100°C / s, heating at a constant temperature of 700-1600°C for 1-90s, and then naturally cooling to room temperature.

[0008] In some embodiments, the nickel precursor includes one or more combinations of nickel acetylacetonate, nickel nitrate, and nickel chloride; the other metal precursors are one or more combinations of acetylacetonate of other metal elements, nitrates of other metal elements, and chlorides of other metal elements; wherein the other metal element is one of manganese, iron, cobalt, and molybdenum; the catalyst carrier is one or a combination of coconut shell charcoal and sawdust charcoal.

[0009] In some embodiments, the mass ratio of the catalyst carrier, the other metal element precursor, and the nickel precursor is 1:(0.1-0.55):(0.1-1).

[0010] In some embodiments, in the mixing step, the solvent is a mixture of water and ethanol in a volume ratio of 1:(0.5-2).

[0011] In some embodiments, in the evaporation step, the mixture is heated and stirred at 70-110° C. for 2-5 hours to evaporate the solvent.

[0012] In some embodiments, the other metal precursor is one or more combinations of acetylacetonate of other metal elements, nitrate of other metal elements, and chloride of other metal elements; wherein the other metal element is manganese; the heating curve of the heating treatment is: heating from room temperature to 1000°C at a heating rate of 75°C / s, and heating at a constant temperature of 1000°C for 30s, and then naturally cooling to room temperature.

[0013] In some embodiments, the preparation method comprises the following steps: Mixing: adding the nickel precursor, the other metal element precursors and the catalyst carrier into the solvent, and performing ultrasonic dispersion for 0.5 to 1 h to uniformly form the mixture; Evaporation to dryness: placing the mixture under heating and stirring at a certain temperature until the solvent is evaporated to dryness; Grinding: scraping the evaporated product with a spatula, transferring it to a mortar and grinding it to obtain the mixture powder; High-temperature heating: the mixture powder is transferred to a graphite tube of a Joule heat tube furnace for high-temperature heating treatment, and the carbon-coated nickel-based catalyst is obtained after cooling.

[0014] The present application also provides a carbon-coated nickel-based catalyst, which is prepared by the rapid preparation method of the carbon-coated nickel-based catalyst as described above.

[0015] In some embodiments, the carbon-coated nickel-based catalyst includes a catalyst support and carbon-coated nickel-based nanoparticles supported on the catalyst support.

[0016] The present application also provides an application of the carbon-coated nickel-based catalyst as described above in biomass pyrolysis to produce hydrogen.

[0017] The rapid preparation method of the carbon-coated nickel-based catalyst provided in the present application has the following beneficial effects compared with the existing technology: The present application provides a rapid preparation method for a carbon-coated nickel-based catalyst, which can prepare high-performance nickel-based catalysts efficiently and in large quantities in a short time. The single preparation takes a short time and the process is simple and fast. The prepared catalyst particles are small and have a relatively uniform size distribution. At the same time, a controllable number of carbon layers are formed on the surface. The catalyst has high activity and good selectivity. It has demonstrated excellent catalytic performance in the application of biomass pyrolysis to produce hydrogen, and thus has broad application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following is a brief introduction to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. The positional relationships described in the drawings in the following description are based on the directions in which the components are drawn in the diagrams, unless otherwise specified.

[0019] Figure 1 TEM images of the products of Examples 1 to 4 and the product of Comparative Example 1.

[0020] Figure 2 The polycrystalline X-ray diffraction patterns of the products of Examples 1 to 4 and the product of Comparative Example 1 are shown.

[0021] Figure 3 This is a comparison chart of the gas volume fraction and gas production results of the products of Examples 1 to 10 when used in biomass pyrolysis to produce hydrogen.

[0022] Figure 4 This is a comparison chart of the gas volume fraction and gas production results of the products of Example 2 and the products of Examples 11 to 13 when used in biomass pyrolysis to produce hydrogen.

[0023] Figure 5 This is a comparison chart of the gas volume fraction and gas production results of the product of Example 2 and the products of Comparative Examples 1 to 5 when used in biomass pyrolysis to produce hydrogen. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0025] The present application provides an example of a method for rapidly preparing a carbon-coated nickel-based catalyst, comprising the following steps: 1. Mixing: Adding the nickel precursor, the other metal element precursors and the catalyst carrier into the solvent, and performing ultrasonic dispersion for 0.5 to 1 h to uniformly form the mixture; The amount of raw materials used is: the mass ratio of catalyst carrier, nickel precursor, and other metal element precursor is 1: (0.1-0.55): (0.1-1). The amount of solvent used is based on the ability to fully impregnate the nickel precursor, other metal element precursors, and catalyst carrier, and to allow the above raw materials to be fully mixed in the solvent system, without excessive restrictions.

[0026] The nickel precursor used includes one or more combinations of nickel acetylacetonate, nickel nitrate, and nickel chloride; the other metal precursors used are one or more combinations of acetylacetonate salts of other metal elements, nitrates of other metal elements, and chlorides of other metal elements; the other metal element is one of manganese, iron, cobalt, and molybdenum; the catalyst carrier used is one or two combinations of coconut shell charcoal and sawdust charcoal. The solvent used is a mixture of water and ethanol in a volume ratio of 1: (0.5-2).

[0027] 2 Evaporation: The mixture is heated and stirred at 70-110° C. for 2-5 hours to evaporate the solvent.

[0028] 3. Grinding: The evaporated product is scraped off with a spatula, transferred to a mortar and ground to obtain the mixture powder; 4. High temperature heating: The mixed powder is transferred to a graphite tube of a Joule heat tube furnace for the high temperature heating treatment, and the carbon-coated nickel-based catalyst is obtained after cooling.

[0029] The temperature rise curve of the high temperature heating treatment is: heating from room temperature to 700-1600°C at a heating rate of 25-100°C / s, heating at a constant temperature of 700-1600°C for 1-90s, and then naturally cooling to room temperature.

[0030] The present application also provides the following embodiments and comparative examples: Example 1 The preparation method of the catalyst of this embodiment comprises the following steps: S1. Weigh 217.2 mg of nickel acetylacetonate, 297.8 mg of manganese acetylacetonate and 400 mg of coconut shell charcoal, add them to a mixed solvent, and disperse them by ultrasonic. The mixed solvent is prepared by mixing 20 mL of water and 20 mL of ethanol.

[0031] S2, placing the above mixture at a temperature of 100° C., heating and stirring for 4 h, until the solvent is evaporated; S3, scraping the evaporated product with a spatula, and further transferring it to a mortar for grinding; S4. The ground mixture powder is transferred to a graphite tube of a Joule heat tube furnace, and rapidly heated to 800°C at a heating rate of 75°C / s, and kept at 800°C for 30s. After cooling to room temperature, a nickel-manganese catalyst sample is obtained, which is recorded as sample 1.

[0032] Embodiments 2 to 4 On the basis of Example 1, the preparation temperature of 800° C. was changed to 1000° C., 1200° C., and 1400° C. respectively, and the other preparation processes and conditions remained unchanged. The obtained samples were recorded as Examples 2 to 4 respectively.

[0033] Embodiments 5 to 7 Examples 5 to 7 are based on Example 2, except that the constant temperature time of 30 s is changed to 15 s, 45 s and 60 s respectively, and other preparation processes and conditions remain unchanged. The obtained samples are respectively recorded as Examples 5 to 7.

[0034] Embodiments 8 to 10 Examples 8 to 10 are based on Example 2, except that the heating rate of 75°C / s is changed to 25°C / s, 50°C / s, and 100°C / s, respectively, and the other preparation processes and conditions remain unchanged. The obtained samples are respectively recorded as Examples 8 to 10.

[0035] Examples 11 to 13 Examples 11 to 13 are based on Example 2, except that 297.8 mg of manganese acetylacetonate is added in place of 150.9 mg of molybdenum acetylacetonate, 303.6 mg of cobalt acetylacetonate, and 299.0 mg of iron acetylacetonate, and the other preparation processes and conditions remain unchanged. The obtained samples are recorded as samples 11 to 13, respectively.

[0036] Comparative Example 1 On the basis of Example 2, the S4 process was changed to: the ground mixture was transferred to a porcelain boat, placed in a conventional tube furnace, heated to 1000°C at a heating rate of 10°C / min in an inert gas atmosphere and calcined for 3 hours, and other preparation steps and conditions remained unchanged. The obtained sample was recorded as the comparative example 1 sample.

[0037] Comparative Example 2 On the basis of Example 2, the raw materials in step S1 (217.2 mg nickel acetylacetonate, 297.8 mg manganese acetylacetonate and 400 mg coconut shell charcoal) were changed to 437.7 mg nickel acetylacetonate and 400 mg coconut shell charcoal, and the other steps and conditions remained unchanged. The obtained sample was recorded as the comparative example 2 sample.

[0038] Comparative Example 3 On the basis of Example 2, the raw materials in step S1 (217.2 mg nickel acetylacetonate, 297.8 mg manganese acetylacetonate and 400 mg coconut shell charcoal) were changed to 641.2 mg manganese acetylacetonate and 400 mg coconut shell charcoal, and the other steps and conditions remained unchanged. The obtained sample was recorded as the comparative example 3 sample.

[0039] Comparative Example 4 ( Figure 5 The name of the experimental group of Comparative Example 4 is recorded as "coconut shell charcoal") In this comparative example 4, coconut shell charcoal of equal mass was used to replace the catalyst prepared in Example 1 to carry out the performance test of biomass pyrolysis hydrogen production application.

[0040] Comparative Example 5 ( Figure 5 The name of the experimental group of Comparative Example 5 is recorded as "no catalyst") In the comparative example 5, no catalyst was added in the biomass pyrolysis hydrogen production application performance test, and a blank experimental group was used as a comparative reference.

[0041] The products obtained in the above examples and comparative examples were subjected to performance tests, and the test results are as follows: one, Figure 1 The transmission electron microscope results of Examples 1 to 4 and Comparative Example 1 are as follows: Figure 1 (ad) respectively show the microscopic morphology of the nickel-manganese catalysts of Examples 1-4 and the product of Comparative Example 1 prepared at heating temperatures of 800°C, 1000°C, 1200°C, and 1400°C; Figure 1 (fj) respectively show the microscopic morphology of the nickel-manganese catalysts of Examples 1 to 4 and the product of Comparative Example 1 at higher magnifications; Figure 1 (ko) shows the particle size statistical distribution diagrams of the nickel-manganese catalysts of Examples 1 to 4 and the product of Comparative Example 1, respectively.

[0042] Figure 1 (ad) shows the microscopic morphology of the nickel-manganese catalyst at different synthesis temperatures in Examples 1-4. It can be seen from the figure that as the synthesis temperature increases, the catalyst particles tend to agglomerate and sinter. When the synthesis temperature is 1000°C, the catalyst particles are most evenly distributed. Figure 1 From the particle size statistical distribution of (kn), it can be seen that the catalyst particles synthesized at 1000°C have the smallest size, which is 16.99±5.91nm.

[0043] Comparative Example 1 uses a conventional tubular furnace to calcine the catalyst at 1000°C for 3h. Although the heating preparation temperature is the same as that of Example 2 (both at 1000°C), Figure 1 (e) and (o) show that compared with the catalyst products synthesized by the rapid carbon thermal shock method in Examples 1 to 4, the nickel-manganese catalyst synthesized in the traditional tubular furnace at the same preparation temperature in Comparative Example 1 also has a more dispersed and uniform particle distribution, but its size is too large, which is not conducive to catalysis.

[0044] In addition, from Figure 1It can be seen from (fj) that the nickel-manganese catalysts synthesized by the rapid carbon thermal shock method in Examples 1 to 4 have carbon layers of different thicknesses formed on their surfaces under different synthesis temperature conditions, and the higher the synthesis temperature, the more carbon layers are covered. However, the catalyst synthesized in the traditional tubular furnace at 1000°C in Comparative Example 1 does not have a corresponding carbon layer coating formed on its surface.

[0045] It is known in the art that appropriate carbon coating helps prevent metal particles from agglomerating and losing, thereby improving the stability of the catalyst. In Comparative Example 1, the catalyst synthesized in a traditional tubular furnace at 1000°C does not have a carbon coating on its surface, which easily causes metal particles to agglomerate and lose, resulting in poor stability and catalytic effect. The poor catalytic performance of Comparative Example 1 is reflected in the gas production performance data when the subsequent product is used as a catalyst in biomass pyrolysis hydrogen production.

[0046] In addition, it is known in the art that appropriate carbon layer coating helps prevent metal particle agglomeration and loss, but too many carbon layers are not conducive to the exposure of active sites. The embodiments of the present application maintain the number of carbon layers within an appropriate range through specific raw material ratios and process control in the preparation method, so that the catalyst product has good catalytic performance, which is specifically reflected in the data results of gas production performance in biomass pyrolysis hydrogen production in subsequent embodiments.

[0047] two, Figure 2 The polycrystalline X-ray diffraction results of Examples 1 to 4 and Comparative Example 1 are as follows: Figure 2 The polycrystalline X-ray diffraction patterns of Examples 1 to 4 and Comparative Example 1 are shown in FIG. Figure 2 As can be seen in (a), Examples 1 to 4 use a rapid carbon thermal shock method to prepare catalyst products. The results of Examples 1 to 4 show that as the synthesis temperature increases, the crystal phase of the product nickel-manganese catalyst changes: In Example 1, when the synthesis temperature is 800°C, the characteristic peaks displayed in the catalyst correspond to the standard crystal phase cards of Ni (JCPDS #No. 87-0712) and MnO (JCPDS # No. 78-0424). In Example 2, when the synthesis temperature is 1000°C, the characteristic peaks of Ni and MnO displayed in the catalyst are more obvious, and the crystallinity is higher. As the synthesis temperature continues to increase, the characteristic peaks of Mn (JCPDS # No. 17-0910) gradually appear in the crystal phase of the catalyst. When the synthesis temperature reaches 1400°C, the main characteristic peaks displayed in the crystal phase of the catalyst are Mn and MnO.

[0048] also, Figure 2 (b) is a comparison of the crystal phase differences between the catalyst product prepared by the rapid carbon thermal shock method in Example 2 and the catalyst product prepared by the traditional tubular furnace reduction method in Comparative Example 1. Figure 2It can be seen in (b) that at the same synthesis temperature, the main characteristic peaks displayed in the catalyst crystal phase prepared by the traditional tubular furnace in Comparative Example 1 are Mn and MnO.

[0049] three, Figures 3 to 5 Comparison of gas volume fraction and gas production results of different catalysts synthesized in Examples 1 to 13 and Comparative Examples 1 to 3 in the application of biomass pyrolysis to produce hydrogen: 1. The products of the examples and comparative examples are used as catalysts in biomass pyrolysis to produce hydrogen. The specific gas production performance test process in the biomass pyrolysis to produce hydrogen application is as follows: A two-stage catalytic device was used to explore the performance differences of the catalyst products of each embodiment and comparative example as catalysts in biomass pyrolysis hydrogen production, wherein poplar sawdust was used as the raw material in an amount of 10 g; the amount of catalyst used in each experimental group was 1 g, the pyrolysis temperature was 500°C, and the catalytic temperature was 550°C.

[0050] 2. Result analysis: 1) Effects of synthesis temperature, constant temperature time and heating rate on the catalytic performance of catalysts: from Figure 3 The test results of Examples 1 to 4 in (a) and (b) show that as the synthesis temperature increases, the volume fraction and yield of H2 show a trend of first increasing and then decreasing. When the synthesis temperature in Example 2 is 1000°C, the volume fraction of H2 generated reaches a peak value of 40.28%, corresponding to an H2 yield of 8.62 mmol / g.

[0051] In Example 2 and Examples 5 to 7, the corresponding constant temperature times at the same heating preparation temperature of 1000° C. are 30 s, 15 s, 45 s and 60 s respectively; Figure 3 (c) and (d) further show the effect of constant temperature time on the catalytic performance. When the constant temperature time is 30 seconds, the volume fraction and production of H2 perform best.

[0052] In Example 2 and Examples 8 to 10, the corresponding heating rates at the same 1000°C heating preparation temperature and 30s constant temperature time are 75°C / s, 25°C / s, 50°C / s, and 100°C / s, respectively; Figure 3 (e) and (f) illustrate the effect of heating rate on catalytic performance. When the heating rate is 75℃ / s, the volume fraction and output of H2 reach the optimal value.

[0053] Figure 3 The above results show that appropriate synthesis temperature, constant temperature time and heating rate are the key factors affecting the catalyst activity.

[0054] 2) Effects of different precursor raw material components on the catalytic performance of biomass pyrolysis hydrogen production catalysts: Examples 11 to 13 use molybdenum acetylacetonate, cobalt acetylacetonate, and iron acetylacetonate to replace the manganese acetylacetonate in Example 2, respectively. Figure 4 The comparative effects of different raw material components on the catalytic performance of biomass pyrolysis to hydrogen production were further demonstrated. Under the same synthesis conditions and metal loading, the nickel-manganese catalyst was the optimal metal combination in all the examples.

[0055] 3) Comparison of the catalytic performance of the products of the rapid carbon thermal shock method used in Example 2 and the traditional tubular furnace reduction method used in Comparative Example 1: Figure 5 (a) and Figure 5 (b) It shows that: compared with the rapid carbon thermal shock method adopted in Example 2, at the same synthesis temperature, the volume fraction of H2 produced by the nickel-manganese catalyst prepared by the traditional tubular furnace reduction method adopted in Comparative Example 1 is only 11.42%, corresponding to an H2 production of 1.25 mmol / g, indicating that the catalytic performance of Comparative Example 1 is significantly poor.

[0056] 4) The precursor raw material components of Example 2 adopt a dual-metal component solution, and the raw material components of Comparative Examples 2 to 3 adopt a single-metal component solution. The catalytic performance of the catalyst products of the two is compared: from Figure 5 (c) and Figure 5 (d) shows the effect of using a single metal component and a bimetallic component in the catalyst on the hydrogen production performance. Compared with the pure nickel catalyst in Comparative Example 2 and the pure manganese catalyst in Comparative Example 3, the hydrogen production effect of the nickel-manganese catalyst in Example 2 is significantly better than the above two. Among them, the volume fraction of H2 produced by the pure nickel catalyst is 25.55%, corresponding to an H2 production of 3.47 mmol / g, while the volume fraction of H2 produced by the pure manganese catalyst is 11.84%, corresponding to an H2 production of 1.21 mmol / g.

[0057] 5) Comparison of the catalytic performance results of the catalyst products of Examples 1 to 13 with the metal-free coconut shell charcoal of Comparative Example 4 and the blank experiment of the catalyst-free condition of Comparative Example 5: from Figure 4 , Figure 5 (c) and Figure 5 As can be seen in (d), compared with the coconut shell charcoal without metal loading and the case without catalyst, the hydrogen production effect of the catalysts in all examples has obvious advantages.

[0058] 4. Summary of Results 1. Comparison between the rapid carbon thermal shock method used in the present embodiment and the traditional tube furnace reduction method of comparative example 1: Compared with the rapid carbon thermal shock method used in the examples of the present application, the catalyst product of the conventional tubular furnace reduction method of Comparative Example 1 has a more dispersed and uniform particle distribution, but its size is too large, which is not conducive to catalysis, and the particle surface does not form a corresponding carbon layer coating, which easily leads to metal particle agglomeration and loss. It can also be seen from the catalytic performance results of the catalyst in the application of biomass pyrolysis hydrogen production that the catalytic performance of the catalyst prepared in Comparative Example 1 is significantly poorer.

[0059] The catalyst product prepared by the rapid carbon thermal shock method used in the present embodiment has a small particle size and a relatively uniform distribution, and its surface is coated with an appropriate carbon layer to prevent metal particles from agglomerating and losing. It can also be seen from the catalytic performance results of the catalyst in the application of biomass pyrolysis hydrogen production that the catalyst prepared in the present embodiment has excellent catalytic activity, and its hydrogen selectivity is about 40%.

[0060] In addition, compared with the traditional tube furnace reduction method, the high temperature treatment step of the present application takes less time and has higher production efficiency.

[0061] 2. This application further optimizes the rapid carbon thermal shock method: The process parameters of the rapid carbon thermal shock method include synthesis temperature, constant temperature time and heating rate, different precursor raw material components, and whether the precursor raw material components use bimetallic components or monometallic components. These factors will affect the activity of the catalyst. This application optimizes the best option for preparing the catalyst carrier by heating the preparation temperature to 1000°C, constant temperature time to 30s, heating rate to 75°C / s, and using nickel-manganese bimetallic components as the precursor raw materials.

[0062] 3. Comparison of the catalytic performance results of the catalyst product of the present application with the blank test results of coconut shell charcoal without metal loading and without catalyst conditions: Compared with the coconut shell charcoal without metal loading and the case of no catalyst, the hydrogen production effect of the embodiment of the present application has obvious advantages.

[0063] In summary, the rapid preparation method of the carbon-coated nickel-based catalyst provided in the present application has at least the following design concepts and beneficial effects: 1. This method adopts high-temperature carbon thermal shock method, which can synthesize catalysts efficiently and in large quantities. The preparation process is simple and fast, overcoming the defects of traditional tubular furnace reduction method, which is time-consuming and inefficient, and has great practical application value; 2. This method uses rapid heating during the preparation process to prepare catalyst particles of small and uniform size, and can achieve carbon coating on the catalyst surface with controllable thickness by regulating the synthesis temperature; 3. This method has a wide range of applications. By replacing different metal precursors, multi-element nickel-based catalysts with different compositions and element ratios can be prepared; 4. The carbon-coated nickel-based catalyst prepared by this method has excellent catalytic performance. The catalyst has high activity and good selectivity, and exhibits excellent catalytic effect in the application of biomass pyrolysis to produce hydrogen.

[0064] In summary, the present application provides an innovative method for rapid batch preparation of carbon-coated nickel-based catalysts. The method can prepare high-performance nickel-based catalysts in a short time, and the single preparation takes a short time and the process is simple and fast. The prepared catalyst particles are small and have a uniform size distribution. At the same time, a controllable number of carbon coatings are formed on the surface. The catalyst has high activity and good selectivity, especially in the application of biomass pyrolysis to produce hydrogen, it exhibits excellent catalytic performance and demonstrates its potential in improving reaction efficiency, thus having broad application potential.

[0065] It should be noted that: The high-temperature carbon thermal shock method used in this article can be implemented using a Joule heat tube furnace device.

[0066] In this article, “~” is used to indicate a numerical range, and the range indicated by this expression includes two endpoint values.

[0067] In addition to the actual selections embodied in the above specific embodiments, the above formulation ranges may be used in the specific implementation of the present application, including but not limited to the above embodiment schemes.

[0068] The specific parameters or some commonly used reagents or raw materials in the above embodiments are specific embodiments or preferred embodiments of the present application, but are not intended to limit the present application. Those skilled in the art may make adaptive adjustments within the scope of the present application.

[0069] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for rapidly preparing a carbon-coated nickel-based catalyst, characterized in that , including the following steps: Mixing: adding nickel precursor, other metal element precursors and catalyst carrier into the solvent and dispersing them evenly to form a mixture; Evaporation to dryness: placing the mixture under heating and stirring at a certain temperature until the solvent is evaporated to dryness; Grinding: Grind the evaporated product to obtain a mixture powder; High temperature heating: subjecting the mixture powder to high temperature heating treatment, and obtaining the carbon-coated nickel-based catalyst after cooling; The temperature rise curve of the high temperature heating treatment is: heating from room temperature to 700-1600°C at a heating rate of 25-100°C / s, heating at a constant temperature of 700-1600°C for 1-90s, and then naturally cooling to room temperature.

2. The rapid preparation method of carbon-coated nickel-based catalyst according to claim 1, characterized in that: The nickel precursor includes one or more combinations of nickel acetylacetonate, nickel nitrate, and nickel chloride; The other metal precursor is one or more combinations of acetylacetonate of other metal elements, nitrate of other metal elements, and chloride of other metal elements; wherein the other metal element is one of manganese, iron, cobalt, and molybdenum; The catalyst carrier is one of coconut shell charcoal and sawdust charcoal or a combination of the two.

3. The rapid preparation method of the carbon-coated nickel-based catalyst according to claim 1, characterized in that: The mass ratio of the catalyst carrier, the nickel precursor and the other metal element precursor is 1:(0.1-0.55):(0.1-1).

4. The rapid preparation method of the carbon-coated nickel-based catalyst according to claim 1, characterized in that: In the mixing step, the solvent is formed by mixing water and ethanol in a volume ratio of 1:(0.5-2).

5. The rapid preparation method of carbon-coated nickel-based catalyst according to claim 1, characterized in that: In the evaporation step, the mixture is heated and stirred at 70-110° C. for 2-5 hours to evaporate the solvent.

6. The rapid preparation method of carbon-coated nickel-based catalyst according to claim 2, characterized in that: The other metal precursor is one or more combinations of acetylacetonate of other metal elements, nitrate of other metal elements, and chloride of other metal elements; wherein the other metal element is manganese; The heating curve of the heating treatment is: heating from room temperature to 1000° C. at a heating rate of 75° C. / s, heating at a constant temperature of 1000° C. for 30 seconds, and then naturally cooling to room temperature.

7. The rapid preparation method of carbon-coated nickel-based catalyst according to claim 1, characterized in that: The following steps are involved: Mixing: adding the nickel precursor, the other metal element precursors and the catalyst carrier into the solvent, and performing ultrasonic dispersion for 0.5 to 1 h to uniformly form the mixture; Evaporation to dryness: placing the mixture under heating and stirring at a certain temperature until the solvent is evaporated to dryness; Grinding: scraping the evaporated product with a spatula, transferring it to a mortar and grinding it to obtain the mixture powder; High-temperature heating: the mixture powder is transferred to a graphite tube of a Joule heat tube furnace for high-temperature heating treatment, and the carbon-coated nickel-based catalyst is obtained after cooling.

8. A carbon-coated nickel-based catalyst, characterized in that: The catalyst is prepared by the rapid preparation method of the carbon-coated nickel-based catalyst as described in any one of claims 1 to 7.

9. The carbon-coated nickel-based catalyst according to claim 8, characterized in that: The invention comprises a catalyst carrier and carbon-coated nickel-based nanoparticles loaded on the catalyst carrier.

10. Use of the carbon-coated nickel-based catalyst according to any one of claims 8 to 9 in biomass pyrolysis to produce hydrogen.